O estudo da paisagem no município de Apucarana-PR : as relações entre a estrutura geoecológica e a organização do espaço - Manosso, Fernando César (2005)
The following work aims, from an integrated analysis, identify and characterize the existing different landscape units or sections in Apucarana which is located in the north region of Paraná state. In this analysis it was used the cartography and geoprocess techniques besides field survey, visit to specialized agencies and oriented interviews. It was identified seven units that were characterized according their horizontal and vertical structure. This structure is represented by the source morphology (shapes and declivity), by the pedologic cover, climate, hydrography and geology. It was collated with the current soil uses and its occupation process aiming to identify the potentials and vulnerabilities of these areas under the social economic activities. The identified landscape sections in the city territory presented different kinds of use and activities. These activities are differentiated by market laws and tax conditions that are regulated by the environmental physical characteristics, for instance: the strong climatic influence in some areas or the predominance of high declivities and appropriated soils in other areas.